Improvement of Severe COVID-19 in an Elderly Man by Sequential Use of Antiviral Drugs. (7th September 2020) - Yatomi, Masakiyo; Takazawa, Tomonori; Yanagisawa, Kunio; Kanamoto, Masafumi; Matsui, Yusuke; Tsukagoshi, Hiroyuki; Saruki, Nobuhiro; Saito, Shigeru; Tokue, Yutaka; Maeno, Toshitaka
Abstract : Although a variety of existing drugs are being tested for patients with coronavirus disease 2019 (COVID-19), no efficacious treatment has been found so far, particularly for severe cases. We report successful recovery in an elderly patient with severe pneumonia requiring mechanical ventilation and extracorporeal membrane oxygenation (ECMO). Despite administration of multiple antiviral drugs, including lopinavir/ritonavir, chloroquine, and favipiravir, the patient's condition did not improve. However, after administration of another antiviral drug, remdesivir, we were able to terminate invasive interventions, including ECMO, and subsequently obtained negative polymerase chain reaction results. Although further validation is needed, remdesivir might be effective in treating COVID-19.